Dewey - Tiles, J. E. (Arguments of the philosophers., 1988)
J.E. Tiles traces the consequences of the dominant characteristic of Dewey's thought, which was his desire to resist thinking of the main aspects of human life in isolation from one another and to resist the institutionalization of their separation. Tiles' book illuminates this major feature of Dewey's philosophy by both relating it to the views of his fellow pragmatists and by contrasting it with doctrines advanced by Aristotle and Hume, as well as philosophers who have risen to prominence since Dewey's death, such as Bernard Williams and Thomas Nagel.